Up-Converting Nanocrystals Modified With Fluorescent Markers for the Detection of Amino Acids: Preparation, Characterization, and Sensing Performance - Fei, YuLang; Wu, Kun; Liu, Liang (Frontiers in Chemistry, 2022)
The present work was devoted to rhodamine-liked chemosensing systems for cysteine (Cys) optical recognition. Aiming at low background light and minimal photobleaching effect, up-converting nanocrystals were firstly synthesized and latterly coated by α-cyclodextrin, and finally used as exciting host. An energy transfer procedure from these nanocrystals and rhodamine sensors had been established via their spectroscopic analysis and emissive decay dynamics comparison. The binding dynamics of our chemosensors for Cys was revealed as an uncomplicated recognition with a stoichiometric ratio of 1 vs. 1. The addition of cysteine increased the emission intensity of chemosensors. As a consequence, luminescence off-on effect with sensing selectivity and linear sensing behavior for Cys was demonstrated. Sulfur modification on our chemosensors was shown effective in improving their selectivity and photostability.